Expression of pluripotency markers on rat C-kit positive amniotic fluid cells from full-term pregnancy / Muhammad Fuad Aris - Aris, Muhammad Fuad (2013)
The discovery of amniotic fluid stem (AFS) cells initiated a new and very promising field in stem cell research. AFS cells from full-term pregnancy serves a better alternative to AFS cells of mid-term gestation as it promises more safety to the patients, less adverse effect and more accessible. Previous study reported that the c-kit positive AF cells demonstrate the expression of pluripotency markers, Oct-4. Although the cells have been successfully expanded in a long period of time, it is still unknown whether the cells maintain its pluripotency in high passage number of cells, in vitro. Here we aim to characterize the expression of these markers on full term c-kit positive amniotic fluid (AF) cells at high passage number at molecular level, using Reverse Transription PCR (RT-PCR). Upon culturing, the c-kit positive cells exhibit heterogenous population of cells, with fibroblastic to epithelial-like morphology. The RNA of the cells were then extracted and subjected to RT-PCR. RT-PCR result demonstrates the absence of Oct-4 and Sox-2 expression in the c-kit positive cells. These data suggest that the passage number influence the potency of the c-kit positive cells. The study also suggests that the c-kit positive cells are able to survive in passage 70 (P 70) and beyond.